THE ROLE OF HISTORY TEACHERS IN SHAPING DIFFERENCES IN STUDENTS' LEARNING INTEREST AT SMA NEGERI 1 PALASA - Yuli; Lukman; Ika Nur Jayanti; Hasan (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This research is motivated by the differences in students' learning interest in history learning, which potentially affect the effectiveness of the learning process, thereby requiring teachers to perform their roles optimally. This study aims to describe the role of history teachers in addressing the differences in learning interest among Grade X students at SMA Negeri 1 Palasa. The conceptual framework refers to Sardiman's theory of teacher roles, which includes the roles of informant, organizer, motivator, director, initiator, transmitter, facilitator, mediator, and evaluator, as well as the theory of learning interest based on indicators of students' feelings of pleasure, involvement, interest, and attention. This study utilized a descriptive qualitative approach. Data were obtained through observation, interviews, and documentation, with informants consisting of one history teacher and nine students selected using a purposive sampling technique. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results showed that the teacher had performed various roles optimally through the use of varied learning methods and media, classroom management, motivation provision, and continuous evaluation, thereby successfully increasing students' attention, involvement, and interest in history learning. Thus, the role of the history teacher contributes significantly to accommodating differences in students' learning interest and creating a more effective learning experience.